PENGGUNAAN MODEL PEMBELAJARAN PEER TEACHING DALAM KEGIATAN EKSTRAKURIKULER MEMBACA AL-QUR’AN DI MTS PAB 1 HELVETIA - Koto, Gita Gania Godelova; Abd Rahman (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to determine the effectiveness of the peer teaching model can affect students' interest, habits and love in reading the Qur'an. Through the peer teaching model, students can learn collaboratively, where students who are more proficient in helping their friends who are still struggling in learning. This research is a descriptive qualitative research. By using observation, interview, and documentation data collection techniques. The results of the study show that the use of this model has succeeded in increasing students' interest and habits in reading the Qur'an. Students who are involved in this program are more motivated to read the Qur'an regularly and are more confident in doing so. The interaction that occurs between the students who teach and the taught creates a relaxed, comfortable, fun and supportive learning environment, so that it can encourage the formation of positive habits in reading the Qur'an. This study aims to determine the effectiveness of the peer teaching model can affect students' interest, habits and love in reading the Qur'an. Through the peer teaching model, students can learn collaboratively, where students who are more proficient in helping their friends who are still struggling in learning. This research is a descriptive qualitative research. By using observation, interview, and documentation data collection techniques. The results of the study show that the use of this model has succeeded in increasing students' interest and habits in reading the Qur'an. Students who are involved in this program are more motivated to read the Qur'an regularly and are more confident in doing so. The interaction that occurs between the students who teach and the taught creates a relaxed, comfortable, fun and supportive learning environment, so that it can encourage the formation of positive habits in reading the Qur'an.